(untitled) (Bangladesh Journal of Medical Science, 2016)
Background: Hepatocellular carcinoma (HCC) is one the most common primary malignancy of the liver and represents the third leading cause of cancer-related deaths worldwide. Incidence rates are highest in East Asia and Sub-Saharan Africa. A number of evidence suggests a possible role of interleukin-6 (IL-6), ?-Fetoprotein (AFP) and Des-?-carboxyprothrombin (DCP) in the pathogenesis of hepatocellular carcinoma (HCC). The high DCP may be related to increase tumour behaviour, such as the presence of vascular invasion and intrahepatic metastasis of HCC cells. Patients and methods: We studied IL-6, AFP and DCP in patients with HCC or in healthy controls. AFP was measured by chemiluminescent immunoassay; Serum IL-6 and DCP were measured by enzyme linked immunosorbent assay in 30 patients with primary hepatocellular carcinoma and 30 normal subjects. Results: IL-6, AFP and DCP were found high in the serum of patients initially diagnosed with HCC (18±9.8), (315.99±594.62) and (26.15±5.01) respectively compared with healthy subjects (4.29±2.10), (3.13±1.27) and (4.25±1.22). A significant positive correlation was found between mean levels of IL- 6 & AFP in HCC (P < 0.05), Combination of IL-6, AFP and DCP improved the sensitivity in diagnosing HCC or predicting future HCC development. Conclusions: IL-6, DCP along with AFP could be considered a promising tumor marker for HCC. DCP is a well recognized tumor marker for the screening and diagnosis of HCC. In particular, the diagnostic value of the test is significantly increased when combined with AFP. Bangladesh Journal of Medical Science Vol.15(2) 2016 p.230-233